Finite-time passivity of dynamic systems. Issue 18 (December 2016) - Hou, Mingzhe; Tan, Feng; Duan, Gunagren
Abstract: This paper is concerned with the concept and properties of finite-time passivity of dynamic systems. As preliminaries, several interesting properties of class K functions are presented. Then, the definition of finite-time passivity is introduced and the relationship between finite-time passivity and finite-time stability is investigated. Furthermore, finite-time passivity properties are investigated for both feedback and parallel connections of finite-time passive components. A numerical example and a realistic example are employed to show the effectiveness of the obtained results.